MAP Development and Direction of Teacher-Based Islamic Education Through Bibliometric Data Analysis - Fauzan Irsyad Wibowo; Nurul Latifatul Inayati; Muhamad Subhi Apriantoro; Afief El Ashfahany (Institut Agama Islam An-Nawawi Purworejo, 2023)
This study aims to determine the mapping of the development and direction of Islamic Religious Education research in publications indexed by scopus data. This study used bibliometric analysis techniques to explore all publications indexed in the Scopus database on Teacher-Based Islamic Religious Education from 1980 to 2023. The data obtained were analyzed using Microsoft Excell and R/R-Studio. VOSviewer is used to perform visual analysis of keyword occurrence and document citations stimulantly. The author found 564 publications that fit the function, subject, and criteria set. The limitation of this study is only taking data sets or metadata to publications indexed by Scopus. Other national and international databases were not taken into account in the study. This study presents a brief overview of the literature that can be accessed by researchers working in the field of Islamic Religious Education and provides recommendations for research.